2019
DOI: 10.1007/s10531-019-01742-7
|View full text |Cite
|
Sign up to set email alerts
|

Urban rain-fed lakes: macro-invertebrate assemblages associated with Egeria najas as indicators of biological integrity in wetlands of Corrientes Province (Argentina)

Abstract: Your article is protected by copyright and all rights are held exclusively by Springer Nature B.V.. This e-offprint is for personal use only and shall not be self-archived in electronic repositories. If you wish to self-archive your article, please use the accepted manuscript version for posting on your own website. You may further deposit the accepted manuscript version in any repository, provided it is only made publicly available 12 months after official publication or later and provided acknowledgement is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Regarding to the taxonomic composition, our results agree with previous studies showing high taxonomical and functional complexity of invertebrate assemblages associated with subtropical macrophytes (Poi et al 2017a, 2021, Gallardo et al 2019, Franceschini et al 2020a.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding to the taxonomic composition, our results agree with previous studies showing high taxonomical and functional complexity of invertebrate assemblages associated with subtropical macrophytes (Poi et al 2017a, 2021, Gallardo et al 2019, Franceschini et al 2020a.…”
Section: Discussionsupporting
confidence: 92%
“…Blanka Gal et al (2020) undertook an interesting study in Europe on benthic fauna at a typical site of urbanization (road crossings), and an assessment of environmental variables showed that road crossings caused habitat changes; it was suggested that these changes were the main drivers of biodiversity patterns. However, Luciana Irene Gallardo et al (2019) showed that seven benthic indices were responsive to urbanization, and benthic community structures were similar to different levels of anthropogenic disturbances in Argentina. In our study, some sampling points were also involved in road crossings, and it was confirmed that human disturbance had a certain effect on the benthic community structure, which was contrary to the study in Argentina, probably because the ecosystem of the Majiagou River is severely shaped by human disturbance, the river length is longer, and the environmental factors are different from those of lakes.…”
Section: Single-factor Significance Test Used For Critical Water Qual...mentioning
confidence: 98%
“…At present, the habitat requirements of urban macro-invertebrates have been researched, and many analysis methods have been used to determine the coupling relationship between the benthic zone and the environment. For example, Gallardo et al (2019) used a non-parametric Kruskal-Wallis test and non-metric multidimensional scaling to study the metrics of the macro-invertebrates' response to urbanization [7]. Van et al (2008) and Andem et al (2022) performed redundancy analyses (RDAs) to reveal the critical relationship between macro-invertebrates and environmental factors such as pH, as well as the type of vegetation and substrates [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of climate, 68.4% of evaluated articles were in temperate regions, 13.2% were in subtropical areas, and 18.4% were in tropical regions (Figures 1, 2B). Nearly all studies of lentic habitats were in temperate areas (Supplementary Table 1), with single articles reporting results from subtropical (Argentina; Gallardo et al, 2019) Since the development of the primarily temperate urban stream syndrome (Meyer et al, 2005;Walsh et al, 2005), there have been recent calls for more attention on tropical urban freshwater systems and the development of the "Southern urban hydrosystem syndrome, " which integrates urban lakes and wetlands in the Global South (Wantzen et al, 2019). Ramírez et al (2009) pointed out that unique characteristics of tropical and island streams, such as their naturally flashier hydrograph, will result in these habitats experiencing urbanization differently.…”
Section: Global Contexts Of Urban Freshwater Biodiversitymentioning
confidence: 99%